Application of the Box-Behnken Design for Optimizing Biodiesel Output from Castor Oil: Analysis and Characterization - Sheyda Rezaei; Seyed Saeid Mohtasebi; Barat Ghobadian; Behzad Nouri; Majid Namdari (Biomechanism and Bioenergy Research)
This study specifically examines the process of producing and analyzing biodiesel made from castor oil using base-catalyzed transesterification. The catalyst used in this process is potassium hydroxide (KOH), and the methanol (CH₃OH) used has a purity of 99.9%. The biodiesel obtained was analyzed extensively to assess its quality. The characterization techniques employed were Gas Chromatography (GC) for compositional analysis, Flash Point measurement for safety assessment, Kinematic Viscosity evaluation for flow properties, and Density determination for mass-volume relationships. To perform a statistical analysis, the Response Surface Method (RSM) was employed to determine the optimal conditions that would yield the highest rate of biodiesel production among the potential solutions. This study focused on three key variables affecting the transesterification process: ultrasonic duty cycle (using a 24 kHz ultrasonic method varying the duty cycle from 20% to 100%), ultrasonic amplitude (varying from 20% to 100%), and reaction time (spanning from 10 to 15 minutes). This investigation achieved a biodiesel yield of 88.38% using a 60% ultrasonic amplitude, a single ultrasonic cycle, and a 15-minute reaction time. The regression model developed can be used to predict biodiesel's percentage conversion.